EFFECT OF CLIMATE CHANGE ON AGRICULTURAL OUTPUT IN ETHIOPIA - Ketema, Adamu Mulu; Negeso, Kasahun Dubale (Journal of Economic Development, Environment and People, 2020)
Currently climate change is known as the major environmental problem the world face. Its effect is openly reduces agricultural output in particular and economic growth in general. The aim of the study was to examine the long run and short run effect of climate change on agricultural output in Ethiopia over a period of 1980-2016. The ARDL approach to co integration was applied to examine the long run and short run effect of climate change on agricultural output. ADF test was used for Unit root test. The finding of bound test shows that there is stable long run relationship between RAGDP, labour force, Mean annual rainfall, Average temperature, agriculture land, and fertilizer input import. The estimated long run model reveals that climate changes have an important effect on agricultural output which is the main contributor of overall GDP of the country. The coefficient of error correction term is -0.738 suggesting about 73.8% percent annual adjustment towards long run equilibrium. The estimate coefficients of short run show that mean annual rainfall have significant effect but average temperature is insignificant effect on output. In the long run both main variable of interest have significant effect on agricultural output with a positive effect from mean annual rainfall and negative effect from average temperature. To reduce the effect of climate change the study recommends government and stakeholders needs to create a specific policies to reduce the effect of climate change especially focus on technological innovation that avert effect of increase in temperature that would result increase on the output and adopting technology at macro and micro level..